Analysis of Open Smash Techniques in Volleyball Coaching College Students - Putra, Martinez Edison; Supriatna, Eka; Puspita Wati, Isti Dwi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
This study aims to determine how the open smash technique in volleyball students. This study aims to obtain information about the series of motion of the open smash technique and to analyze the open smash technique. This type of research is a descriptive quantitative survey method. The sample in this study consisted of 7 volleyball coaching students who had the following criteria: (1) Tanjungpura University PKO men's volleyball core team, (2) had participated in competitions according to PBVSI rules. The data analysis technique used in this research is descriptive statistics. The results showed that the average volleyball coaching student took the prefix stage where the distance from the net was 3.47 m, with a 3-step approach, swing angle 87°, repulsion angle 149°, elbow angle 80°, back angle 162°, jump height 53 cm, the distance between ball and hand about 35 cm, and landing using 2 feet.